Future studies on identifying potential land for urban development using GIS (Case study: Kerman city) - esmaeeil kamali; omeid samandari; sadegh; morteza sarhadi (تحقیقات کاربردی علوم جغرافیایی)
Assessment of the land's capacity for urban development in the sense of objectifying the potential of the land is among the expected and executable applications. On the other hand, increasing urban population, followed by the growth of cities, due to the expansion of urban development makes moving toward the principles of sustainable development an indispensable act. Kerman as one of Iran's major cities encountering with limited natural and human development, is not an exception. Thus, it is essential to take into account its development structure. This study aims to identify the fertile lands for future development of the city of Kerman. This study is functional in nature and purpose and descriptive-analytic in methodology. In order to achieve the purpose of the study, the method of fuzzy Analytic Hierarchy Process (AHP) and Boolean was employed, and finally by combination of maps, appropriate lands for future development of Kerman were identified. The results of this study showed that the lands located in South, Southwest, and North and northwest of the city of Kerman are in a better position for future development compared to other parts of the city.